Utilização de luz ultravioleta contínua (UV-C) e luz pulsada para conservação de mangas CV. Tommy Atkins minimamente processadas - Souza, Julianna Freire de [UNESP] (2014)
Mango (Mangifera indica L.) is a tropical fruit with great expression in the national market presenting a great potential for fresh-cut includes selection operations, washing, sorting, cutting (slicing), sanitization, centrifugation, refrigeration and packaging and presents itself as an alternative to increase the consumption of mango in the domestic market, as it offers the consumer a product practical and convenient which has no characteristics freshness changed. Therefore, for the success of minimally processed products is important to keep their fresh state and microbiological safe. The aim of this study was to evaluate the effects of application of UV-C radiation and pulsed light on qualitative, physicochemical, physiological and microbiological characteristics, antioxidant bioactive properties in minimally processed cv. Tommy Atkins mangoes. To achieve these goals, the work was composed of four experimental trials. The initial test was carried out with the objective of defining the best packaging for storing the processed mango; The second test was carried out with the objective of defining the intensity of UV-C light that better control the biochemical alterations of the product; The third experimental trial was carried out in order to observe the efficiency of UV-C in eliminating microbial contaminants; and the last test was carried out in order to observe the effect of the pulsed light in the control biochemical changes in minimally processed mango. The storage of minimally processed mangoes was done at 5° C and 80% RH for 12 days. For tests 1, 2 and 4 at 0, 3, 6, 9 and 12 days analyzes of color of pulp, total soluble solids, titratable acidity, ascorbic acid, pH, activity of peroxidase, polyphenol oxidase, pectin methyl esterase, phenylalanine ammonia lyase, total antioxidant potential and accumulation of CO2 in the package were performed. For microbiological analysis, test 3, the ...